Promoting agricultural and rural modernization through application of information and communication technologies in China - Qu, Dongyu; Wang, Xiaobing; Kang, Chunpeng; Liu, Yang (International Journal of Agricultural and Biological Engineering, 2018)
China has obtained remarkable major achievements of agricultural and rural development in the past five years, such as advance in agricultural supply-side structural reform, breakthroughs in rural reform, headway in urban-rural integration development, improvement in rural public services and social undertakings, progress in poverty alleviation, a new level in agricultural trade. Specifically speaking, China is witnessing the following development in Information and Communication Technology (ICT) application in rural areas: Internet infrastructure is strengthened; E-commerce in rural areas is thriving; rural information service is upgraded; A solid progress has been made in Agricultural Internet of Things and rapid deployment of big-data technology. This paper summarizes the experiences gained in the development of agricultural and rural informatization in China. Based on this review, some suggestions were presented: Firstly, improving policy systems through innovation; secondly, strengthening ICT infrastructure; thirdly, giving full play to the primary role of market; fourthly, carrying out pilot demonstration and trainings. At the same time, the problems faced by rural e-commerce development were also pointed out.Keywords: ICT application, agriculture and rural development, modernization, agricultural informatization, rural informatization, internet of things, e-commerce DOI: 10.25165/j.ijabe.20181106.4228Citation: Qu D Y, Wang X B, Kang C P, Liu Y. Promoting agricultural and rural modernization through application of information and communication technologies in China. Int J Agric & Biol Eng, 2018; 11(6): 1–4.